2021
DOI: 10.1108/jpmd-07-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

An image worth a thousand words? Expressions of stakeholder identity perspectives in place image descriptions

Abstract: Purpose This paper aims to explore how place identity can be expressed in residents’ place image descriptions, addressing differences and similarities in place identity expressions between residents’ descriptions of the image of their place and the image of the place as described to others. Design/methodology/approach In-depth interviews were conducted with residents of a Swedish city. Place image descriptions were analyzed through thematic analysis. Findings Different types of identity perspectives manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…First, the study confirms the importance of understanding the complex place image of residents to capture positive and negative place attributes, to identify strong selling points and actions needed to retain residents (Ragusa, 2022;Strandberg & Ek Styvén, 2021;Stylidis, Belhassen, & Shani, 2015). Failure to take into account the perspective of residents leads to a practitioner-stakeholder perception gap (Peighambari, Sattari, Foster, & Wallström, 2016), image communication incongruent with residents' perceptions (Palmer et al, 2013), and serious negative implications for sustainable place development (Stylidis et al, 2015).…”
Section: Implications For Management Practicementioning
confidence: 56%
See 3 more Smart Citations
“…First, the study confirms the importance of understanding the complex place image of residents to capture positive and negative place attributes, to identify strong selling points and actions needed to retain residents (Ragusa, 2022;Strandberg & Ek Styvén, 2021;Stylidis, Belhassen, & Shani, 2015). Failure to take into account the perspective of residents leads to a practitioner-stakeholder perception gap (Peighambari, Sattari, Foster, & Wallström, 2016), image communication incongruent with residents' perceptions (Palmer et al, 2013), and serious negative implications for sustainable place development (Stylidis et al, 2015).…”
Section: Implications For Management Practicementioning
confidence: 56%
“…This could explain why previous research found a link between identifying as a resident of a city and place commitment (Tournois & Rollero, 2019), while the current study shows no direct effect of self-congruity on likelihood to stay. This finding emphasizes the difference between personal and social identification with a place (Strandberg & Ek Styvén, 2021) and highlights the importance of careful consideration of which construct to apply when operationalizing identification with a place. The current findings suggest that different facets of self-congruity are not interchangeable, that focusing on only a specific facet of congruity may bias the results, and that self-congruity with both the place image/itself (Droseltis & Vignoles, 2010), its brand personality (Wassler & Hung, 2015), and its users (Sirgy & Su, 2000) may well be antecedents of an overall place self-congruity construct.…”
Section: Implications For Theorymentioning
confidence: 80%
See 2 more Smart Citations